Analysis of the bacterial biofilm formation in different models of the in vitro culture - Bogut, Agnieszka; Magryś, Agnieszka (European Journal of Clinical and Experimental Medicine, 2021)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Microtiter plate assay (MPA) remains one of workhorses of in vitro biofilm research but it requires optimization of experimental conditions to fulfill the biofilm formation requirements of different bacterial pathogens. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim was to determine the effect of TSB and RPMI1640 culture media and selected culture variables (O2 vs. 5% CO2, extended incubation time) on the biofilm production by bacteria commonly involved in biofilm-related infections: Enterococcus faecalis (EF), Escherichia coli (EC), Staphylococcus aureus (SA), Pseudomonas aeruginosa (PA), Klebsiella pneumoniae (KP). <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The investigation was performed using the MPA with crystal violet. Results. Statistically significant (p<0.05) increase in biofilm production between 24h and 72h time points was observed for EF (TSBo2, RPMIo2 and RPMIco2 ), EC (TSBo2 ), SA (TSBo2, TSBco2), KP (TSBo2, TSBco2), PA (RPMIco2, TSBco2). The TSB caused a significantly greater stimulation of biofilm production compared to RPM1640. It outcompeted RPMI1640 irrespective of the atmospheric conditions for SA and KP and under aerobic conditions for EF. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Although the TSB provided the most optimal conditions for biofilm production, the process was influenced by the strain type, atmospheric conditions and period of cultivation which limits the ability to design a single universal model of the in vitro biofilm investigation.